The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/nau.10111
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous tibial nerve stimulation in the treatment of overactive bladder: Urodynamic data

Abstract: PTNS could not abolish DI. PTNS increased cystometric capacity and delayed the onset of DI. Cystometry seemed useful to select good candidates: patients without DI or with late DI onset proved to be the best candidates for PTNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 18 publications
1
72
0
7
Order By: Relevance
“…[13] More than 30 studies regarding PTNS have been published. The earliest ones are case series or single-arm efficacy studies, [14][15][16] three are randomized, controlled trials, [9,17,18] and two are long-term follow-up studies of patients who were responders in the overactive bladder innovative therapy (OrBIT) and sham effectiveness in the treatment of overactive bladder symptoms (SUmiT) trials. [19,20] Over half of the patients receiving PTNS therapy in the SUmiT trial, a randomized, double-blinded, sham controlled study, reported moderate or marked improvement in bladder symptoms (54.5% in PTNS patients vs. 20.9% in sham, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[13] More than 30 studies regarding PTNS have been published. The earliest ones are case series or single-arm efficacy studies, [14][15][16] three are randomized, controlled trials, [9,17,18] and two are long-term follow-up studies of patients who were responders in the overactive bladder innovative therapy (OrBIT) and sham effectiveness in the treatment of overactive bladder symptoms (SUmiT) trials. [19,20] Over half of the patients receiving PTNS therapy in the SUmiT trial, a randomized, double-blinded, sham controlled study, reported moderate or marked improvement in bladder symptoms (54.5% in PTNS patients vs. 20.9% in sham, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies to suggest that patient-related outcomes are similar whether or not there is an urodynamic diagnosis of DO in patients with OAB, following a variety of treatment options. [84][85][86][87] A comparable situation exists for stress incontinence, whereupon non-invasive assessments alone were found to be not inferior to UDS for outcomes at 1 year in a randomised controlled trial (RCT).…”
Section: Effect Of Tests On Subsequent Treatment Pathwaymentioning
confidence: 99%
“…These are the most likely areas in which the therapeutic effect of neuromodulation of the bladder by PTNS acts, and this 30-minute stimulus already has a beneficial effect 16,17 . Authors who have studied the effects of PTNS consider it a good therapeutic option for the treatment of OAB because of its low cost and the lack of the side effects of drug therapy 4,10,11,14,15,[18][19][20][21][22][23][24] . In comparison with other electrical stimulation techniques, it has the advantage of generating less discomfort and embarrassment to patients because it is not applied to the genital area 4,10,[22][23][24] .…”
Section: Introductionmentioning
confidence: 99%